THE DEVELOPMENT OF ELECTROCHEMISTRY PRACTICAL SUBJECT IN SMALL SCALE THEREWITH THREE-WORLD ANIMATION VIDEO - Firdaus
The essential constrains that inhibit chemistry learning are different conditions of laboratories, insufficiency of experiment tools, and, in some schools, unavailability of experiment tools either because they are difficult to obtain or because of being expensive. Moreover, there are some chemistry materials difficult for students to grasp because they require an understanding of atom-level behaviors, such as electrochemistry. In this research, small-scale chemistry experiment tools were created, applied in a learning package that included videos with animation and 3-world method-based explanation (macroscopic, sub-microscopic, symbol). It was carried out to facilitate the students in learning and understanding electrochemistry, particularly Galvani cell. The stages undertaken included a preliminary stage, that is, the creation of microplate and salt bridge by using an injection device, cork, tissue, and pipette. The next stage was finding the smallest concentration value of the material that still give a cell E value, that is, by making varying concentrations of Cu2+, Zn2+, Fe2+, and Al2+ solutions at a concentration range of 1 M – 0.01 M. The cell potentials were measured by a mini digital multimeter for Cu2+ - Zn2+, Cu2+- Fe2+, Cu – Al, and Fe2+ -Zn2+ systems. Also conducted in this research was varying concentrations for reduced metals and oxidized metals. That was conducted to determine the inclinations of reduction and oxidation properties of the metals on the resulted potential values. From the minimal concentration obtained, an experimental video and its animation was made by using Animation software. Its explanation was prepared by a 3-world method, and then summarized into a complete learning package by using a Windows Movie Maker software. From the measurement of cell potential, the smallest concentration for Cu2+ - Zn2+ that still gave a good potential reading was obtained, that is, 0.04 M by a volume of 5 ml with a cell potential value of 1.08 V. The results for other systems were respectively as follows: for Cu2+ - Fe2+, the concentration was 0.3 M by a volume of 20 mL with a cell potential value of 0.72 V; for Fe2+ - Zn2+ , the concentration was 0.06 M by a volume 5 mL with a cell potential value of 0.35 V. The experimental data of Galvani cell form Cu-Zn, Fe-Zn, Cu-Fe, and Cu-Al systems showed that the higher the concentration of oxidized metal ion, the smaller is its cell potential. This research produced experimental devices of a microplate and a complete small-scale Galvani cell learning package including a video with animation and a 3-world method-based explanation. It is hoped that the results of this research could provide an equal chance to students in diverse regions to conduct experiments at their schools, and facilitate them in understanding principles and phenomena occurring in Galvani cell. In addition, it is also hoped that the product of this research attracts the attention of teachers to develop small scale chemistry experimental tools and similar learning packages for other chemistry materials.